LANDSCAPES OF CITY AND LANSIA THAT SUFFER (THE CASE OF FATHER'S SPION GLASS, HUANG YONGMEI WORK) - Hin Goan Gunawan (Fakultas Sastra Universitas Darma Persada, 2019)
Abstract. City is a symbol of modernity. The revival of the Urban Fiction genre in contemporary Chinese literature is driven by writers of the 1970s. It portrays not only urban landscapes with the beauty in their works, but also exposes the souls that suffer in urban spaces. As a symbol of a modern, advanced and civilized life portrayed in Huang Yongmei's short story